ANALYSIS OF FINANCIAL PERFORMANCE BEFORE AND AFTER MERGER AND ACQUISITION IN PUBLIC COMPANIES LISTED IN INDONESIA STOCK EXCHANGE (PERIOD 2013 – 2017) - Hartasya, Maudina Tri (Jurnal Manajemen Update, 2020)
One of external factor method that each companies could do in strategic planning is, doing the merger and acquisition (M&A). In Merger and Acquisition, two companies become more valuable than two separate companies. By the joint of two companies, it is expected that they can achieve greater efficiency. Financial performance is a high consideration to attract investors. Then, firm value is a high standard for a company to be perceived as good by investors and stakeholders. Every strategy taken will affect the firm value. In this study, the author does not only analyse the financial performance before and after merger and acquisition, but the author is also analyse whether the strategy—merger and acquisition—affects the firm value. The ratios used for this research are Current Ratio (CR), Debt to Asset Ratio (DAR), Debt to Equity Ratio (DER), Total Asset Turnover Ratio (TATO), Return on Asset (ROA), Net Profit Margin (NPM), and (Operating Profit Margin). The Data is non-parametric, so the hypotheses testing is Wilcoxon Signed Rank Test for period two years before and two years after Merger and Acquisition. For analyzing the firm value, the financial ratios are only CR, DAR, DER, ROA, TATO, and Merger and Acquisition as dummy variable. Multiple regression is used to test the hypotheses, with the classical assumption test that has to be tested prior to multiple regression. The data is obtained from public companies listed in Indonesia Stock Exchange and doing Merger and Acquisiton in period 2013 – 2017. ROA has significance difference before and after merger and acquisition. While for analyzing the firm value, separately the result shows that only Debt to Equity Ratio strategy affects the firm value. Keywords: Merger, acquisition, financial performance, Current Ratio, Debt to Equity Ratio, Debt to Asset Ratio, Return on Asset, Net Profit Margin, Operating Profit Margin